Immune thrombocytopenic purpura: A case report - Robert McLeish; Deborah Boyd (Elsevier, 2022)
We report a case of immune thrombocytopenic purpura (ITP) in a 5-year-old female presenting with a maxillofacial injury. The patient attended through the emergency department with marked right periorbital ecchymosis and swelling following a head first collision. This case highlights the importance of early diagnosis of ITP, as well as consideration of a haematological cause in the presence of unexplained or excessive bruising.